Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1242/jcs.03250
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and molecular interactions of the Erv41p-Erv46p complex involved in transport between the endoplasmic reticulum and Golgi complex

Abstract: Erv41p and Erv46p are integral membrane proteins conserved across species. They were originally identified as abundant constituents of COPII-coated vesicles, and form a complex which cycles between the endoplasmic reticulum and Golgi complex. Yeast strains lacking these proteins are viable but display subtle secretory phenotypes. In order to obtain information about possible biological roles of this protein complex in endoplasmic reticulum to Golgi transport, we employed the Synthetic Genetic Array approach to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 60 publications
1
26
0
Order By: Relevance
“…An endoplasmic reticulum-Golgi intermediate compartment (ERGIC) domain was located in the N-terminus, and an endoplasmic reticulum vesicle transporter domain (COPII coated_ERV) was located in the C-terminus. These domains are also present in several other proteins, such as ERGIC-32 in mouse and Erv41p and Erv46p in yeast, and play important roles in protein sorting, folding, and glycoprotein processing in the ER and early Golgi complex [39], [40]. The functions of two trans-membrane regions of the BdPDIL8-1 are assumed to replace the function of the N-terminal signal peptide and C-terminal KDEL retrieval sequence, both of which are involved in the early protein secretory pathway between ER, ERGIC, and the Golgi complex.…”
Section: Resultsmentioning
confidence: 99%
“…An endoplasmic reticulum-Golgi intermediate compartment (ERGIC) domain was located in the N-terminus, and an endoplasmic reticulum vesicle transporter domain (COPII coated_ERV) was located in the C-terminus. These domains are also present in several other proteins, such as ERGIC-32 in mouse and Erv41p and Erv46p in yeast, and play important roles in protein sorting, folding, and glycoprotein processing in the ER and early Golgi complex [39], [40]. The functions of two trans-membrane regions of the BdPDIL8-1 are assumed to replace the function of the N-terminal signal peptide and C-terminal KDEL retrieval sequence, both of which are involved in the early protein secretory pathway between ER, ERGIC, and the Golgi complex.…”
Section: Resultsmentioning
confidence: 99%
“…ERGIC3 has large domains in the ER lumen, and its short N- and C-terminal tail sequences expose to the cytosol and the two transmembrane segments each, which would be available for protein-protein interactions in the ER lumen or membrane [26]. Through the systematic and serial screening, we found that the ERGIC3 mRNA and protein were highly over-expressed in lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…ERGIC3 belongs to the family of the ER vesicle (Erv) proteins (Otte et al, 2001). ERGIC3 interacts with ERGIC2 (Welsh et al, 2006) and ERGIC1 (Breuza et al, 2004) and forms a heterotrimeric protein complex. Both isoforms contain ERGIC_N domain and COPIIcoated_ERV domain (figure 3) which is conserved from fungi to humans.…”
Section: Descriptionmentioning
confidence: 99%
“…ERGIC3 works in close on junction with ERGIC2 and together they form a complex which cycles between the endoplasmic reticulum and cis-Golgi network. Both are integral membrane proteins with two membrane spanning segments each, short Nand C-terminal tails expose to the cytosol, and large central luminal domains (figure 3) (Welsh et al, 2006). …”
Section: Descriptionmentioning
confidence: 99%
See 1 more Smart Citation